A theoretical mechanistic study of [K ⊂ [2.2.2]]+ enantiomerization. (28th September 2021) - Balović, Jelena; Ćoćić, Dušan; Đorđević, Slađana; Radenković, Slavko; van Eldik, Rudi; Puchta, Ralph
Abstract: Density functional calculations at three different levels of theory (B3LYP/LANL2DZp, B3LYP‐GD3/LANL2DZp, and ωB97XD/def2tzvp) were applied to different conformers of the Lehn‐type macrobicyclic polyether cryptate complex [K ⊂ [2.2.2]] + to construct the enantiomerization pathway and to compute the energy barrier for the change in symmetry. Changes in the conformation of the investigated complex are discussed in terms of energy and geometric criteria, where changes in the structures follow a trend of activation energies prohibiting the achiral pathways. The investigated D 3 ‐symmetric cryptate [K ⊂ [2.2.2]] + shows enantiomerization through an all chiral five step pathway with two local minima ( C 2 and C 2 ′) and three C 1 transition states ending in the D 3 ′‐symmetric cryptate [K ⊂ [2.2.2]] +, the mirror image of the starting structure. The potential achiral transition states are higher order saddle points with a minimum twice as high in energy as an all‐chiral path. This study unambiguously accounts for Lehn's NMR data showing fluxionality of the studied complex. The obtained results were further rationalized by means of energy decomposition analysis (EDA) and natural bond orbital (NBO) calculations performed for the metal cation and the host in its different conformations. Abstract : The D 3 structure of [K ⊂ [2.2.2]] + undergoes enantiomerization via an all‐chiral pathway to reach D 3 ′. The suggested pathway explains J.‐M. Lehn's experimental NMR data from the early days of supramolecular chemistry.